2019
DOI: 10.1200/jco.18.02306
|View full text |Cite
|
Sign up to set email alerts
|

Final Analysis of DeCOG-SLT Trial: No Survival Benefit for Complete Lymph Node Dissection in Patients With Melanoma With Positive Sentinel Node

Abstract: PURPOSE We have previously reported on the 3-year results of the phase III German Dermatologic Cooperative Oncology Group trial (DeCOG; ClinicalTrials.gov identifier: NCT02434107 ) comparing distant metastasis-free survival (DMFS), recurrence-free survival (RFS), and overall survival (OS) in patients with positive sentinel lymph-node biopsy who were randomly assigned to complete lymph node dissection (CLND) or observation. Here, we report the final analysis with 72 months of median follow up. PATIENTS AND METH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
129
2
22

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(162 citation statements)
references
References 20 publications
9
129
2
22
Order By: Relevance
“…[34,35]. In the DeCOG study, 68% of patients in the observation arm and 65% in the CLND arm were free of distant metastases after 5 years of follow-up [38,39]. In the MSLT-II, 86% of the patients in both study groups (CLND or observation) were alive after 3 years [33].…”
Section: Sentinel Lymph Node Biopsymentioning
confidence: 99%
“…[34,35]. In the DeCOG study, 68% of patients in the observation arm and 65% in the CLND arm were free of distant metastases after 5 years of follow-up [38,39]. In the MSLT-II, 86% of the patients in both study groups (CLND or observation) were alive after 3 years [33].…”
Section: Sentinel Lymph Node Biopsymentioning
confidence: 99%
“…B, Same patient as in Figure VI, the excisional defect following melanoma resection was reconstructed with scalp rotation flap and can be associated with formidable morbidity due to seroma formation, wound infection or lymphedema. 45…”
Section: Treatmentmentioning
confidence: 99%
“…It carries significant morbidity, however, not all patients derive actual survival benefits from this undertaking. One logical explanation for this is that the positive SLNB may be the harbinger of a more widespread metastatic disease where lymph node dissection simply does not address the distant metastasis 1,3,[45][46][47]. 9 | METASTATIC EVALUATION AND THE "TNM" STAGING SYSTEM IN SCALP MELANOMA Scalp melanomas are known to be very aggressive and often have high mitotic rate.…”
mentioning
confidence: 99%
“…However, with publications of the German Dermatologic Cooperative Oncology Group (DeCOG) trial [3] and Multicenter Selective Lymphadenectomy-2 trial (MSLT-2) [4], indications for CLND continue to evolve. The latest DeCOG trial results with 72 months follow-up have shown that CLND compared to observation in patients with positive SNB is not associated with increased overall survival [5]. MSLT-2 showed that CLND provides prognostic information as well as improved regional disease control [4], while final analysis of DeCOG-SLT trial concluded that a therapeutic benefit for CLND could not be demonstrated [5].…”
Section: Introductionmentioning
confidence: 99%
“…The latest DeCOG trial results with 72 months follow-up have shown that CLND compared to observation in patients with positive SNB is not associated with increased overall survival [5]. MSLT-2 showed that CLND provides prognostic information as well as improved regional disease control [4], while final analysis of DeCOG-SLT trial concluded that a therapeutic benefit for CLND could not be demonstrated [5]. However, there are differences in SNB protocols and clinicopathologic features of the patient cohorts between centres.…”
Section: Introductionmentioning
confidence: 99%